Molecular phylogeography of white‐lipped tree viper (Trimeresurus; Viperidae). (1st January 2016) - Zhu, Fei; Liu, Qin; Che, Jing; Zhang, Liang; Chen, Xin; Yan, Fang; Murphy, Robert; Guo, Cong; Guo, Peng
Abstract : The white‐lipped tree viper ( Trimeresurus albolabris ) is one of the most common venomous snakes with medicine importance in South East Asia. To explore the genetic diversity, population structure and evolutionary history of Trimeresurus albolabris, we collected 98 samples from 27 localities covering its entire distribution. Two mitochondrial gene fragments (cyt‐b and ND‐4) and two nuclear genes (RAG‐1 and NT‐3) were sequenced and analysed. Bayesian inference and maximum‐likelihood methods were employed to reconstruct the phylogenetic relationships among populations based on the two mitochondrial fragments, and the median‐joining networks were depicted using nuclear genes. Divergence date and ancestral area were estimated, and the population demographic history was inferred. Both phylogenetic analyses consistently uncovered that Trimeresurus albolabris was monophyletics, with five geographically structured lineages. Divergence date and ancestral area estimation indicated that T. albolabris originated in northern Thailand and eastern Myanmar at c . 7.15 Ma. Population dynamics analyses showed the southern China lineage has experienced population expansion and contraction, but the others have not. Both the interglacial expansion and the highly heterogeneous habitats resulting from the uplift of the Plateau played a joint role in shaping the present distribution and population structure. The evolutionary history of T. albolabris can be explained by a pattern of two direction dispersal: first from North to South, and then from West to East.